The double isolation of Venezuela's foreign policy - Cardozo, Elsa (2016)
This article focuses on President Hugo Chavez's foreign policy, analyzing the ambiguities related to its "Democratic Revolution" Program gives Chavez's revolutionary, and politically and economically anti-liberal stance the president, according to Cardoso, is permanently in risk of international and national isolation. The contradictory features of his foreign policy can be seen in Venezuela's bilateral relations with Colombia, the United States, and Cuba.